Hypoxia-induced endoplasmic reticulum stress characterizes a necrotic phenotype of pancreatic cancer - Kong, Bo; Cheng, Tao; Wu, Weiwei; Regel, Ivonne; Raulefs, Susanne; Friess, Helmut; Erkan, Murat Mert; Esposito, Irene; Kleeff, Jörg H.; Michalski, Christoph (OncoTarget, 2015)
ER stress; VEGFA; hypoxia; necrosis; pancreatic cancer
Gesehen am 15.07.2020
"Published: October 05, 2015"